PENGUATAN PRODUK, PEMASARAN DIGITAL, DAN SDM DALAM PENGEMBANGAN DESA WISATA KAMPOENG DELING - Hilwa Rohmahdiniyah Nur Azizah; Winda Purwaning Suhairiya; Agung Winarno; Wening Patmi Rahayu (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This community service initiative aims to enhance the capacity of Kampoeng Deling as a bamboo-based tourism village through the development of products, digital marketing, human resources (HR), and governance. The main challenges faced by the partners include the lack of flagship products, limited digital marketing capabilities, and suboptimal organizational structures and management systems. The method used was a qualitative approach employing an explanatory participatory method combined with Participatory Rural Appraisal (PRA). Data collection techniques included observation, interviews, and focus group discussions. The results of the activity show that flagship products in the form of bamboo souvenir packages have been developed, a product catalog and Instagram-based digital marketing media have been created, and an organizational structure and Standard Operating Procedures (SOPs) have been established as management guidelines. This initiative has had a positive impact on increasing product value-added, expanding market reach, and strengthening institutional governance. Thus, the integration of product development, digital marketing, and human resource capacity building has proven to be an effective strategy in supporting the sustainable development of the Kampoeng Deling tourism village. ABSTRAK Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kapasitas Kampoeng Deling sebagai desa wisata berbasis bambu melalui penguatan produk, pemasaran digital, serta sumber daya manusia (SDM) dan tata kelola. Permasalahan utama yang dihadapi mitra meliputi belum adanya produk unggulan, keterbatasan pemasaran digital, serta belum optimalnya struktur organisasi dan sistem pengelolaan. Metode yang digunakan adalah pendekatan kualitatif dengan metode partisipatif bersifat explanatory yang dipaduka dengan Participatory Rural Appraisal (PRA). Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan diskusi kelompok. Hasil kegiatan menunjukkan bahwa telah terbentuk produk unggulan berupa paket souvenir bambu, tersusunnya katalog produk dan media pemasaran digital berbasis Instagram, serta terbentuknya struktur organisasi dan Standar Operasional Prosedur (SOP) sebagai pedoman pengelolaan. Kegiatan ini memberikan dampak positif terhadap peningkatan nilai tambah produk, perluasan jangkauan pemasaran, serta penguatan tata kelola kelembagaan. Dengan demikian, integrasi pengembangan produk, pemasaran digital, dan penguatan SDM menjadi strategi efektif dalam mendukung keberlanjutan pengembangan desa wisata Kampoeng Deling.